Fenestropathy of Voltage-Gated Sodium Channels - Gamal El-Din, Tamer M.; Lenaeus, Michael J. (Frontiers in Pharmacology, 2022)
Voltage-gated sodium channels (Nav) are responsible for the initiation and propagation of action potentials in excitable cells. From pain to the heartbeat, these integral membrane proteins are the ignition stations for every sensation and action in human bodies. Nav mutations lead to a multitude of diseases - including chronic pain, cardiac arrhythmia, and seizure disorders - and a wide variety of currently used therapeutics block Nav. Nav fenestrations, which are pathways that connect the plasma membrane to the central cavity in the pore domain, were discovered through functional studies more than forty years ago and once thought to be simple pathways. A variety of recent genetic, structural, and pharmacological data, however, shows that these fenestrations are actually key functional regions of Nav that modulate drug binding, lipid binding, and influence gating behaviors. The discovery of disease mutations that cause arrhythmias by altering amino acid residues that line the fenestrations of Nav1.5, in particular, indicates that fenestrations may play a critical role in channel’s gating, and that individual genetic variation may also influence drug access through the fenestrations for resting/inactivated state block. In this review, we will discuss the channelopathies associated with these fenestrations, which we collectively name “Fenestropathy”, and how changes in the fenestrations associated with the opening of the intracellular gate could modulate the state-dependent ingress and egress of drugs binding in the central cavity of voltage gated sodium channels.